A bibliometric analysis of global publications on financial management in sports clubs - Mustafa Ertan Tabuk (Universidad de Murcia, 2024)
As sports clubs' assets grow, their financial resources must be managed professionally. The aim of this study was to analyze all scientific publications between 2000 and 2020 and to make a holistic analysis of financial management in sports clubs using data obtained within the scope of the study. Information graphics and explanatory bibliometric networks were created. The study was conducted using the document analysis method in order to determine the current status of "financial management in sports clubs" among academic publications. The study identified the most frequently used keywords in publications, the most cited authors, and the most published journals, institutes, and countries. The most cited studies in the literature focus on non-profit organizations, resource capacity and use, management of financial results, management challenges related to human, financial, infrastructure and cultural resources, investment decisions in professional football and football clubs with strong financial capacity. It can be stated that the financial management of sports, both professional and amateur (non-profit organizations, sports development, and peace-oriented structures), focuses on the creation and use of resources. This article provides important information for decision-makers in the sports industry.